1970
DOI: 10.3171/jns.1970.32.3.0304
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamics and Metabolism Following Experimental Head Injury

Abstract: HE pathogenesis of cerebral concussion has long been debated. The present experiments were undertaken to clarify the nature of acute cerebral disorders resulting from head injury. Concussion was defined by Denny-Brown as a "transitory and reversible nervous reaction with immediate onset following physical stress of sufficient violence and brevity, and characterized by progressive recovery thereafter. ''~ There are two main theories concerning the pathogenesis of concussion: the excitation theory of Walker, et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…However, no correlation could be demonstrated between the degree of diffuse brain swelling, classified according to Marshall et al [25], to metabolic parameters such as cerebral lactate differences and cerebral oxygen extraction, to ICE or to outcome. As confirmed by numerous experimental studies, lactate in brain tissue and CSF is increased by cerebral trauma [5,15,27,29,33,45]. These elevated cerebral levels of lactate may contribute to brain acidosis after' trauma, which has been implicated by several authors as a causative factor in injury to the central nervous system [20,26,28,32,35,38].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, no correlation could be demonstrated between the degree of diffuse brain swelling, classified according to Marshall et al [25], to metabolic parameters such as cerebral lactate differences and cerebral oxygen extraction, to ICE or to outcome. As confirmed by numerous experimental studies, lactate in brain tissue and CSF is increased by cerebral trauma [5,15,27,29,33,45]. These elevated cerebral levels of lactate may contribute to brain acidosis after' trauma, which has been implicated by several authors as a causative factor in injury to the central nervous system [20,26,28,32,35,38].…”
Section: Discussionmentioning
confidence: 76%
“…Increased cerebral formation of lactate was related to the severity of trauma in experimental as well as clinical investigations [27,36]. In most of the clinical studies, increased cerebral lactate levels were assessed by measurements in cerebrospinal fluid (CSF) [6,8,21,34].…”
Section: Introductionmentioning
confidence: 99%
“…The mean cerebral arteriovenous O2 content difference was within the normal range and did not change after OHP. Due to the low value of the CBF, the mean CMRO2 was low before (1.73 ± 1.32 ml/100 g/ min) and after OHP (1.67 ± 1.53 ml/100 g/min), compared to the accepted normal value of 3.3±0.4 ml/100 g/min [22]. Pre-OHP and post-OHP CMRO2 values did not differ significantly.…”
Section: Changes In Cmro> Cmrgl and Cmrlactmentioning
confidence: 91%
“…This is in keeping with the results in our three patients with bilateral hemispheric lesions and low CBF: two of them, with a total of four studies, showed an increased flow after OHP, while the third patient was uninfluenced. Indirect evidence for this effect of OHP on low CBF can be found in its demonstrated capacity of reducing increased intracranial pressure [10,23,25,26,28,29], and experi mental brain edema [29], two major factors of brain posttraumatic ischemia [7,20,22], Regarding CMRO2, CMRGL and CMRLact, the disparate patterns of response to OHP primarily reflect the diverse pathological and circulatory status of the brain region covered by the probe. However, the relative inaccuracy of this usual method for measuring cerebral metabolic rates must be borne in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Meyer etal. [11] have reported significant CBF reduction following severe concussion or contusion produced by an airgun in baboons, with only a slight increase in CBF during the first minute following mild concussions. Nilsson and Nordstrom [12] have observed an immediate 50% increase in CBF following concussion produced by an accelerated piston in rats, followed by a marked reduction for 40 rain, after which CBF tended to recover toward baseline.…”
Section: Cerebral Blood Flow Responses To Injurymentioning
confidence: 99%